Diffusion of bisphenol-A (BPA) through an HDPE geomembrane. Issue 6 (14th June 2016) - Saheli, P. T.; Rowe, R. K.; Rutter, A.
Abstract : Partitioning and diffusion experiments performed on bisphenol A (BPA) and high-density polyethylene (HDPE) geomembrane are reported. The tests indicate no measurable partitioning to the geomembrane and an estimated upper bound permeation coefficient is 3 × 10 −15  m 2 /s. This low value of permeation coefficient suggests that an HDPE geomembrane will be a very effective diffusive barrier for BPA for the conditions examined. Partitioning tests on BPA in a mixture with 12 other phenolic compounds did not show any measurable change in partitioning of BPA to the geomembrane due to the presence of the other compounds. The partitioning coefficients for phenolic compounds examined range from 0.61 for 2-methylphenol to 31 for 2, 3, 4, 6-tetrachlorophenol and the diffusion coefficients ranged from 9.3 × 10 −15  m 2 /s for 2, 3, 4, 6-tetrachlorophenol and pentachlorophenol to 9.3 × 10 −14  m 2 /s for 2- methylphenol.